The Ecophysiological Response of Two Invasive Submerged Plants to Light and Nitrogen - Szabó, Sándor; Peeters, Edwin T. H. M.; Borics, Gábor; Veres, Szilvia; Nagy, Péter Tamás; Lukács, Balázs András (Frontiers in Plant Science, 2020)
Two submerged Elodea species have small differences in their ecophysiological responses when exposed to individual environmental factors. However, field observations showed that under eutrophic conditions with low light availability, Elodea canadensis could be displaced by E. nuttallii. Here we investigated the combined effect of environmental factors on the ecophysiological response of the two species in order to explain the differences in their invasion successes. We cultivated the plants in aquaria containing five different nitrogen (N) concentrations and incubated at five different light intensities. For both species increasing nitrogen concentrations resulted in increased relative growth rate (RGR), chlorophyll concentration, and actual photochemical efficiency of photosystem II (ΦPSII), however, they produced less roots. Lowering light intensity resulted in a lower RGR, root production and nutrient removal. In contrast, chlorophyll concentration in the leaves, and ΦPSII increased. The main difference between the two Elodea species was that the light compensation point (Ic) and weight loss in the dark were significantly higher and photochemical efficiency and chlorophyll concentration were significantly lower for E. canadensis than for E. nuttallii, indicating that the latter can survive under much more shady and hypertrophic conditions. The change in nitrogen concentration of the media and in tissue concentration of the plants indicated that E. nuttallii has a higher nitrogen removal capacity. The ecophysiological differences between the two species can be an explanation for invasion success of E. nuttallii over E. canadensis and thus may explain why the latter is replaced by the first.